Trade liberalization and the environment in Vietnam - Jha, Shreyasi (Policy research working paper, 2006)
"Vietnam's integration with the international economy has increased significantly over the past decade, aided by substantial liberalization of trade, and appears set to increase further as trade-expanding measures take full effect. This dramatic shift in Vietnam's trading patterns has important implications for the environment and use of natural resources. This paper offers a systematic analysis of the trading and investment patterns to give a broader understanding of the environmental implications of greater openness of the economy during the past decade. The results suggest increasing manufacturing and export activity in water and toxic pollution-intensive sectors compared with the less pollution-intensive sectors. The story is, on the surface, consistent with the changing composition of Vietnamese production and exports away from traditional sectors and toward pollution-intensive manufacturing (especially leather and textiles). The paper also highlights the need to consider strengthening environmental policies while further trade liberalization is being contemplated through Vietnam's joining of the World Trade Organization. "--World Bank web site